Internet Traffic Dynamics in Wireless Sensor Networks Based on Energy Efficiency with Routing Protocols - Manu Singh; Vanitha K.; Bhargabjyoti Saikia; Arpana Mishra; Sameeksha Verma; Sachin Gupta (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Wireless sensor network (WSN) has emerged as a promising technology for the recent advances in electronics, networking, and information technologies. This dissertation offers multiple methods for modelling various elements of WSN traffic in the area of traffic analysis and modelling for WSNs. This research proposed novel technique in analysing the internet traffic dynamics of WSN by energy efficient and routing of the network. Here the traffic analysis is carried out using dynamic distance vector protocol and the routing is enhanced with energy efficiency using clustering based lightweight spatio energy efficient routing technique. The experimental analysis has been carried out in terms of throughput, traffic analysis, energy efficiency, packet delivery ratio.